Poetry, automaticity and the animal body: Jacques Derrida with Emily Dickinson. Issue 5 (28th May 2018) - Parkin-Gounelas, Ruth
ABSTRACT: The article begins by addressing Derrida's enigmatic assertion that 'thinking concerning the animal … derives from poetry'. Derrida's late engagement with the animal question brought into play the body, rhythm, the poetic 'event' and, fundamentally, the automatic or involuntary nature of much human experience. Challenging Jacques Lacan's distinction between human 'response' and animal 'reaction', Derrida undermined cherished notions of human singularity, agency and knowledge by emphasising our animal vulnerability – to death, to our inhabitation by the inorganic and to a disavowed reactionality. Poetry, he contends, like the animal induces 'pathos' in the original Greek sense of passivity or involuntarity. To illustrate the singularity of the poetic event as defined by Derrida, the article focuses on a reading of Emily Dickinson's 'A narrow Fellow in the Grass', in particular its rhythmic resonances. Dickinson's poems, especially those depicting human-animal encounters, manipulate rhythmic variation within the ballad format to convey vacillations between anthropomorphic 'fellowship' between species and fellowship of a more threatening kind, a shared animal reactionality which exposes our vulnerability. Just as the cat triggers shame and vertigo in Derrida standing naked before its gaze, similarly Dickinson's poetry provokes visceral reactions which strip us of comforting assumptions about human knowledge.